Injectable hydrogels for targeted delivering of therapeutic molecules for tissue engineering and disease treatment. (12th November 2019) - Mavlyanova, Rukhshona; Yang, Rufeng; Tao, Tao; Aquib, Md; Kesse, Samuel; Maviah, Mily Bazezy Joelle; Boakye‐Yiadom, Kofi Oti; Farooq, Muhammad Asim; Wang, Bo
Abstract : Hydrogels are cross‐linked three‐dimensional polymeric networks that play a vital role in solving the pharmacological and clinical limitations of the existing systems due to their unique physical properties such as affinity for biological fluids, tunable porous nature, high water content, ease of preparation, flexibility, and biocompatibility. Hydrogel also mimics the living natural tissue, which opens several opportunities for its use in biomedical areas. Injectable hydrogel allows temporal control and exceptional spatial arrangements and can offset hitches with established hydrogel‐based drug delivery systems. Here, we review the recent development of injectable hydrogels and their significance in the delivery of therapeutics such as cells, genes, and drug molecules and how these innovatory systems can complement the current delivery systems.